Effects of Alcohol Consumption Frequency on Health Index in Korean Women - Hee-Ju KWON; Ik-Rae CHO; Hyo-Joo PARK; Tae-Young KIM (Tehran University of Medical Sciences, 2016)
Background: In this study, we examined the status of Korean women's alcohol consumption and identified the physical changes they undergo according to the level of consumption. The results of this study may thus be used as raw data to effectively control women' drinking habits. Methods: This study consists of a secondary analysis using data from female participants in the 6th Korea National Health and Nutrition Examination Survey, which was conducted by the Korea Centers for Disease Control and Prevention(2013-2014, V-2). In total, 863 women were finally selected to analyze their anthropometric data [height, body weight, body mass index (BMI), and waist circumference], blood parameters (total cholesterol, triglyceride, and feeding glucose), blood pressure profile (systolic/diastolic), and nutrients (carbohydrate, protein, lipid, and total energy intake). Results: Women's alcohol consumption contributed significantly to an increase in body weight, body fat, and BMI as well as to an increase in total energy intake resulting from increased fat consumption. Further, the systolic blood pressure increased significantly when women were exposed to alcohol. Conclusion: The results of this study suggest that alcohol consumption in women is associated with a range of adverse health implications. Notably, an increase in drinking frequency significantly affects their body weight, blood parameters, and nutrients, thus posing substantial health risks to the women, including obesity. Therefore, the Korean government should help women curve their drinking habits through regular training and campaigns.   Keywords: Korean women, Alcohol consumption, Health index